Curse motifs in Galatians: an investigation into Paul's rhetorical strategies - Kim, Seon Yong (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Titel -- Acknowledgments -- Table of Contents -- List of Abbreviations -- Note on Translations and Citations -- Chapter 1: Introduction -- Chapter 2: "Anomalies" and a Call for a Paradigm Shift: Assessing the New Perspective on Paul and the Post-New Perspective -- 2.1 Introduction -- 2.2 Problem 1: Appeals to the Notions of incompatibility, Incongruity, and Conditionality and the Failure to Grasp Sanders's Stress on the Importance of Presupposition -- 2.3 Problem 2: Interpretive Slipperiness That Cannot Account for the Gap between "Need Not" (Gentile Believers Need Not Be Circumcised) and "Must Not" (Gentile Converts Must Not Get Circumcision) -- 2.3 Problem 3: The Problem of the Rhetoric of Re- -- Chapter 3: The Curse Motif in Galatians and the Significance of the Galatians' Cultural Assumptions in Analysis of Paul's Argumentation: A Preliminary Survey -- 3.1 Introduction -- 3.2 The Prevalence of the Curse Motif in Galatians -- 3.3 Who Was the Main Target of Paul's Argument? -- Chapter 4: The Distinctive Rhetorical Features in Galatians -- 4.1 Introduction -- 4.2 Paul's Negative Portrait of the Agitators as Evil Magicians -- 4.3 Paul's Repeated Reversal of the Traditional Jewish Reading of Scripture -- 4.4 The Normative Character of the Pauline Gospel -- Chapter 5: Reading Galatians through the Lens of the Curse Theme -- 5.1 Christ Giving Himself Up: A New Reading of Gal 1:4 and Its Implications for Other Themes in Galatians -- 5.2 Paul's Argument from Example and Experience: Highlighting the Fragility of the Relationship with Christ -- 5.3 Slavery of Galatians and the στοιχεῖα: A Rhetorical Reading of Gal 4:4 and 4:9 -- 5.4 Reading Gal 3:10-14 through the Lens of Rhetorical Stasis Theory -- 5.5 Gal 4:21-31: Paul Synthesizes the Previous Argument by Retelling the Story of Hagar and Sarah.